The computer model of a neutron fluxes forming system on a linear electron accelerator - S. P. Gokov; V. M. Horbach; Yu. G. Kazarinov; V. V. Kantemirov; V. I. Kasilov; L. N. Kolpakova; O. A. Lyukhtan; E. V. Tsiats’ko (Ядерна фізика та енергетика)
A computer model of the system for generating neutron fluxes at the output of a linear electron accelerator has been developed in the Geant4 and PhysList QGSP BIC HP programming environment. With the help of the model, a number of virtual experiments on 107 primary neutrons were carried out. The dependence of the ratio of the number of neutrons, incident on the detector with a reflector to the number of neutrons without a reflector on the radius of curvature of the hemispherical dome of the reflector is determined, which makes it possible to establish the optimal dimensions of the working area. The energy spectra of neutrons incident on the detector are determined. It has been established that when using a graphite reflector 30 × 30 × 30 cm in size with a radius of curvature of the hemispherical dome of 5 cm, the number of neutrons at the location of the detector increases by 16.9 %, and the neutron background in the accelerator bunker decreases by 2.5 times, which is in good agreement with the real experiment made. Such a decrease in the radiation background, according to sanitary standards, will make it possible to increase the accelerator current by 2.5 times and increase the neutron flux.